Audit pemakaian antibiotika di unit penyakit dalam RSUP dr. Sardjito Yogyakarta=Antibiotics Audit at theDepartement of Internal Medicine Dr Sardjito Hospital, Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1988)
ABSTRACT This study was designed to improve the quality of antibiotic treatment through the development of an audit system. This study was an uncontrolled experimental design in nature with a descriptive emphasis on various aspects of the pattern of antibiotic utilization. In short, guidelines for the use of antibiotics were developed as a mean of intervention to the prescriber in improving the rationality of their antibiotic prescribing. The pattern of antibiotic use during the pre and post implementation period of the guidance was compared to see whether any improvement could be achieved The guidelines covered several issues including indication, use, dosage, treatment of side effects and possible drug interaction. These, in fact, were developed and finally accepted by all prescribers in the unit. Assessment of the use of antibiotics was performed by the prescribers themselves on the bases of the guidelines. Any treatment diviation from the protocol in the guidelines which could not be accounted for by the prescriber was classified as "deficiency'. The data concerning "deficiency" treatment during 2 month period before the implementation of the guidelines was collected retrospectively from the medical records, and compared to that obtained prospectively during 2 month period after the introduction of the guideline. Altogether there were 11 prescribers involved, but only seven completed the evaluation. The assessment, therefore was made to prescribtions made by these 7 prescribers only. The proportion of "derwienty" treatment before the introduction of the guideline was 35,6% of the antibiotic prescriblions and decreased significantly to 21% after the guidelines. In conclusion, therefore, the development of antibiotic treatment guideline could reduce the "deficiency" treatment, indicating an improvement in the quality of antibiotic the therapy.